Chemical profiles of essential oils of marjoram (Origanum majorana) and oregano (Origanum vulgare) obtained by hydrodistillation and supercritical CO2. Issue 5 (3rd September 2017) - Busatta, Cassiano; Barbosa, Juliana; Cardoso, Rafael Imlau; Paroul, Natalia; Rodrigues, Maria; Oliveira, Débora de; Oliveira, José Vladimir de; Cansian, Rogério Luis
Abstract: The objective of this work was to evaluate and compare the chemical profile of essential oils of marjoram ( Origanum majorana ) and oregano ( Origanum vulgare ) obtained by hydrodistillation and supercritical CO2 . The yield of marjoram and oregano essential oils obtained by supercritical CO2 was higher than those from hydrodistillation. Both essential oils presented similar chemical profiles. The major compound was terpinen-4-ol in essential oil obtained by hydrodistillation and cis -sabinene hydrate in the essential oil obtained by supercritical CO2, to both species. The hydrodistillation method showed higher quantitative differences between the extraction fractions in relation to the supercritical extraction. The extracts obtained by supercritical CO2 presented higher concentrations of oxygenated monoterpenes, without significant differences between fraction 1 and 2. A comparison between the extraction methods showed a higher extraction capacity of monoterpene hydrocarbons by hydrodistillation and oxygenated monoterpenes by supercritical extraction, allowing optimizing the extraction of compounds of interest by the choice of the most adequate extraction method.